Cost accounting. - Inman, Mark Lee (CIMA series., 1989)
Cost Accounting, Second Edition covers information and terminologies that prepare students for the final Level of the Accounting Technicians examinations, and the Level 1 Cost Accounting paper for the Chartered Association of Certified Accountants.